Look at the stars little bear - Swift, Christine; Endersby, Frank (London : Alligator Products, Ltd., 2024)
Little Bear who is scared of the dark, he hears noises and sees things moving. But Mummy Bear helps him count the stars and soon Little Bear is no longer scared and cant wait for night time
Primary
Keywords: Bears -- Fiction; Bedtime -- Fiction; Fear of the dark -- Fiction; Imagination in children -- Fiction; Mother and child -- Fiction